Transient Abnormal Myelopoiesis in a Neonate without Down Syndrome - Shrestha, Rupesh (Journal of Nepal Paediatric Society, 2018)
Transient abnormal myelopoiesis (TAM) also known as transient myeloproliferative disorder (TMD), a unique transient neonatal preleukaemic disorder characterized by clonal proliferation of megakaryoblasts, has been usually described to be associated with Down syndrome neonates. However, there are case reports of it occurring in neonates without Down phenotype, who are either mosaic for trisomy 21 or have trisomy 21 restricted to leukemic clone. This case report presents a case of TAM in a phenotypically normal neonate who presented in respiratory distress with features of tumour lysis syndrome (TLS) immediately after birth who was treated symptomatically and had spontaneous remission within three months.